(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Biaxially loaded reinforced concrete columns are structural components impacted by axial compression and bending forces in two directions. This study involves retrofitting of preloaded columns using ferrocement jacketing consists of high performance mortar and reinforced with geogrid mesh. Six reinforced concrete short columns (150*150*1700) mm are cast with concrete bracket at each end. Two of them served as control columns which are loaded till failure, while the other four columns are preloaded and then retrofitted. They are preloaded up to (65 & 85) % of the total failure loads of control specimens. The eccentricity value of loading changed between (30) mm and (70) mm for the both axes. The results proved that using this technique of retrofitting increases the ultimate carrying capacity of the preloaded columns up to (38.8) % comparing to the control specimens. It also improves their crack resistance and failure behavior. Finally, the experimental results are compared with the analytical results obtained from finite element analysis (FEA) using ABAQUS program.